Inside Out: Sentiments of Wives on Their Husband's Detention from the Anti-Drug Campaign - Francisco, Jesusa C. (Review of Women's Studies; Vol 28 (2018): Review of Women's Studies Volume XXVIII (2018), 2023)
The proliferation of the illegal drug trade in the Philippines made President Duterte enforce an anti-drug campaign or Oplan Tokhang after he took office on June 30, 2016. Those who surrendered were rehabilitated, but some of those who were arrested and are still in detention have wives who are suffering in silence because their plight has not been given attention because the most visible victims in the anti-drug campaign are their husbands. This study aims to explore the impact of the husbands' incarceration due to the anti-drug campaign on their wives, to identify the immediate and primary needs of the wives after their husbands' detention, as well as their means of coping. The study uses qualitative research methods with phenomenology as its approach for analysis. The data was gathered from semi-structured, face-to-face interviews with eight women who are married to detainees of the government's anti-drug campaign in the Municipality of Hagonoy. Member checking for validation of data results was also conducted. An analysis of the interview transcripts gave way to the 3 Dimensions of Husbandwives Phenomenon (3DHP). It shows the themes - categorized as impacts - on the wives from their husbands' detention, which are as follows: (1) familial responsibilities, (2) emotional anxiety, and (3) personal growth goals.